Political Elites in Disaster News: A Framing Analysis of the 2010 Mt. Merapi Eruption News in TVRI Yogyakarta - Dwi Nurrahmi Kusumastuti (Department of Communications, Universitas Islam Indonesia, 2022)
The paper focuses on how a local station of Indonesian public television, i.e., TVRI Yogyakarta, framed the news about the 2010 Mt. Merapi eruption. Applying a textual analysis model developed by Zhongdang Pan and Gerald M. Kosicki, the paper analyses a news program of TVRI Yogyakarta called ‘Berita Yogya’ from 26th October to 14th November 2010. The study finds that TVRI Yogyakarta has emphasized news figures or the element of ‘who’ in the news, especially concerning governments and political parties’ elites. Related to this framing, TVRI Yogyakarta has frequently highlighted the topic of disaster aid, especially from the government and political parties. TVRI has accentuated the solidarity and care from government and political parties through the headlines and news about the ceremonies of handing over disaster aid from the political elites to the survivors. It shows that, instead of performing its role as a public media during the crisis of the Mt. Merapi eruption, TVRI Yogyakarta was imprisoned in the New Order ideology of TVRI as a state television.